Do the Gulf Oil-Producing Countries Influence Regional Growth? : The Impact of Financial and Remittance Flows - Ilahi, Nadeem; Shendy, Riham (Washington, D.C. : International Monetary Fund, 2008)
This paper tests the association between the Gulf Cooperation Council (GCC) countries' financial and remittance outflows and regional growth in the Middle East. The findings, based on 35-year panel data, indicate that growth rates of real GDP, private consumption and private investment in regional countries are strongly associated with remittance outflows from and the accumulation of financial surpluses in the GCC. Unlike in other developing and emerging market countries, growth in regional countries is not influenced by growth in the North, and is not export led. Linkages with the GCC could help sustain output growth in the regional countries in the face of the global economic slowdown and oil price shocks and could provide diversification gains to international capital seeking markets uncorrelated with Northern and emerging market countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet